Simultaneous determination of seven bile acids to study the effect of ivermectin on their plasma levels in rat by UHPLC–MS/MS - T. V. Radhakrishna Mullapudi; Punna Rao Ravi; Ganapathi Thipparapu (Journal of Analytical Science and Technology, 2023)
Abstract Bile acids (BAs) are considered to be important diagnostic biomarkers to understand the pathophysiology of hepatobiliary and metabolic diseases. BAs regulate lipid and glucose metabolism by binding to farnesoid X receptor (FXR). To date, there were no reports on the effect of an exogenous FXR modulator, ivermectin (IVM), on the plasma BA profiles in rats. To explore the effect of IVM on plasma BA levels in rat, an ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC–MS/MS) method was developed and validated for simultaneous determination of seven major BAs in rat plasma. The developed method was selective, specific, accurate and precise for the quantification of plasma BAs. Sprague–Dawley rats were orally administered with IVM at a dose of 5 mg/kg once a day for 14 days and the plasma BAs were determined before and after IVM exposure using developed UHPLC–MS/MS method. Once-daily administration of IVM for 14 days resulted in significant reduction in cholic acid and deoxycholic acid levels while glycodeoxycholic acid and taurodeoxycholic acid levels were not affected. Interestingly, tauro-α-muricholic acid and tauro-β-muricholic acid levels were significantly increased. This study revealed that IVM has an important effect on plasma BA profiles in rats. This report provides an analytical methodology that can be applied to investigate the effect of drugs or pathophysiological factors on plasma BA levels.